2015
DOI: 10.1007/s11302-015-9478-z
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of ATP hydrolysis decreases adenosine A1 receptor tonus favoring cholinergic nerve hyperactivity in the obstructed human urinary bladder

Abstract: This study was designed to investigate whether reduced adenosine formation linked to deficits in extracellular ATP hydrolysis by NTPDases contributes to detrusor neuromodulatory changes associated with bladder outlet obstruction in men with benign prostatic hyperplasia (BPH). The kinetics of ATP catabolism and adenosine formation as well as the role of P1 receptor agonists on muscle tension and nerve-evoked [ ) or (2) extracellular adenosine accumulation with dipyridamole or EHNA, as these drugs inhibit adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 51 publications
(78 reference statements)
7
30
0
Order By: Relevance
“…Alternatively, rather than a temporal change in ATP release with duration of diabetes, it may be that ATP metabolism is affected. While to our knowledge there have been no reports of altered ecto‐ATPase activity within the bladder in diabetes, activity of these enzymes is altered in bladder tissues from patients with overactive bladder . Regardless of the underlying mechanism, here we demonstrate temporal changes in intraluminal ATP in diabetic bladder dysfunction, which has not been previously reported.…”
Section: Discussionsupporting
confidence: 48%
“…Alternatively, rather than a temporal change in ATP release with duration of diabetes, it may be that ATP metabolism is affected. While to our knowledge there have been no reports of altered ecto‐ATPase activity within the bladder in diabetes, activity of these enzymes is altered in bladder tissues from patients with overactive bladder . Regardless of the underlying mechanism, here we demonstrate temporal changes in intraluminal ATP in diabetic bladder dysfunction, which has not been previously reported.…”
Section: Discussionsupporting
confidence: 48%
“…release through the activation of prejunctional A 1 receptors on bladder cholinergic nerves (Silva et al, 2017;Silva-Ramos et al, 2015) was confirmed further in the present study. Figure 3 shows that transmitter release inhibition caused by mirabegron (0.1 μM, Figure 3b), isoprenaline (1 μM, Figure 3c), and FSK (3 μM, Figure 3d 1 μM), isoprenaline (1 μM), and forskolin (3 μM) were applied 6 min before S 2 either in the absence or in the presence of selective inhibitors of PKA (H-89, 10 μM), EPAC (ESI-09, 10 μM), and ENT1 (Dipy, 0.5 μM), as well as of the adenosine A 1 receptor antagonist, DPCPX (0.1 μM).…”
Section: The Involvement Of Adenosine Release Via Ent1 Transporters Isupporting
confidence: 86%
“…Indirect evidence suggests that ATP is released at lower stimulation rates, compared to those releasing ACh (Calvert et al, ; Chakrabarty et al, ; Pakzad et al, ). There is more direct evidence that the PDE‐5 inhibitor sildenafil abolishes nerve‐mediated ATP release (Chakrabarty et al, ); however, this should be set against the observation that ACh is also modulated by agents such as adenosine (Silva‐Ramos et al, ). The development of amperometric ATP‐selective electrodes potentially allows for the real‐time measurement of nerve‐mediated ATP release in detrusor muscle.…”
Section: Introductionmentioning
confidence: 99%